Implantation character attitude student in the fourth grade through habbit in the elementary School Seroja Serang City - Iskini Haudoka; Suparno Suparno; Hosnan Hosnan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The advancement of development nowadays has brought many positive and negative things for everyone. The positive impact can bring progress both in information and communication technology. Whereas, the negativity can lead to setbacks in society. One of them is politeness culture and mutual respect among the society. Indonesia is popular with its culture of manners and politeness but recently this culture has begun to disappear. For example,in several cases, students are no longer considered their teacher as a role model at school. Therefore, this research was intended to embed students’ moral and character through a habituation method. This method was expected to build the students’ character better.